Burkitt's lymphoma in Brazil: Strong association with Epstein-Barr virus - Bacchi, M. M.; Bacchi, C. E.; Alvarenga, M.; Miranda, R.; Chen, Y. Y.; Weiss, L. M. (Williams & Wilkins, 1996)
The incidence of Burkitt's lymphoma (BL) in Brazil is intermediate between the endemic form of equatorial Africa and the sporadic form in the United States, To characterize these lymphomas, we evaluated the clinical, morphologic, and immunohistochemical features of 24 Brazilian cases of BL, We also analyzed the cases for the presence of Epstein-Barr virus (EBV)-RNA using a highly sensitive and specific method of in situ hybridization, Most cases presented with involvement of intraabdominal organs, similar to the sporadic form of BL, EBV-RNA was detected in 17 of 24 cases (71%) in all or virtually all the tumor cells, This prevalence of EBV-positivity in our cases is intermediate between the endemic form of BL in equatorial Africa (100%) and the sporadic form in the United States (30%), These findings suggest that EBV plays an important role in the pathogenesis of BL in Brazil, This intermediate incidence of EBV infection may explain in part the differences of incidence of BL in different geographic regions.
Keywords: Brazil; Burkitt's lymphoma; Epstein-Barr virus; in situ hybridization